Sosialisasi Literasi Politik Bagi Siswa SMKN 1 Pangandaran Menjelang Pemilihan Kepala Daerah 2024 - Fahrudin, Atef; Lisnarini, Naurah (Wahana Dedikasi: Jurnal PkM Ilmu Kependidikan, 2024)
The "Compact: Communication Impact" political literacy program was held to enhance the political awareness of 12th-grade students at SMKN 1 Pangandaran ahead of the 2024 Regional Election. Political literacy is crucial to fostering quality democratic participation, especially among youth. The program included Focus Group Discussions (FGDs), debates, expert sessions, and pre- and post-tests to measure outcomes. A total of 34 students participated, aiming to improve their ability to detect hoaxes, analyze political issues, and understand their role as first-time voters. Evaluation results showed a 6.05% increase in post-test scores, indicating improved political literacy. Students also shifted from apathetic to more critical and active political attitudes. This program successfully provided relevant political knowledge and practical skills, becoming a model for future youth political literacy initiatives.